Free conjunctival grafts in the repair of leaking filtering blebs - Costa,Renato C. (2003)
PURPOSE: To evaluate the effectiveness of free conjunctival grafting for leaking conjunctival blebs following trabeculectomy. METHODS: Retrospective study of seven patients with leaking conjunctival blebs that were repaired by free conjunctival grafting. The effectiveness of this procedure in stopping the bleb leak, maintaining satisfactory intraocular pressure (IOP), maintaining satisfactory anterior chamber depth, and preserving vision was evaluated. RESULTS: Free conjunctival grafting appeared to have stopped the bleb leak in 6 patients (85.7%), maintained satisfactory IOP in 5 patients (71.4%), maintained satisfactory anterior chamber depth in all patients, and preserved pretreatment vision in 3 patients. CONCLUSIONS: Free conjunctival grafting appears to be an effective method to treat leaking blebs, without loss of IOP control.